2019
DOI: 10.4067/s0718-58392019000200288
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of seed traits to the genetic diversity of a segregating population of Passiflora spp.

Abstract: Genetic diversity can be investigated early using seed traits, an important aspect of sexually propagated species. In this context, plant breeders aim at the production of new varieties using seeds with good germination and vigor. The present study was thus designed to examine the genetic diversity of a segregating population from a cross between Passiflora edulis Sims and P. setacea DC. based on seed morphological-and physiological-quality responses. Seventeen seed morphology variables were evaluated via digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 16 publications
3
13
0
1
Order By: Relevance
“…The results obtained in this study and those described by Torres et al (2019), Fachi et al (2019, and Krause et al (2017) clearly demonstrate that the contribution of each variable to determine genetic divergence can vary according to species, genotype, and family.…”
Section: Digital Phenotyping Meanssupporting
confidence: 76%
See 1 more Smart Citation
“…The results obtained in this study and those described by Torres et al (2019), Fachi et al (2019, and Krause et al (2017) clearly demonstrate that the contribution of each variable to determine genetic divergence can vary according to species, genotype, and family.…”
Section: Digital Phenotyping Meanssupporting
confidence: 76%
“…The gray level difference method evaluates the texture features that describe the size and highlights of the image (Bharathi and Subashini, 2013 Torres et al (2019) evaluated genetic diversity in a segregating population of passion fruit based on seed morphological and physiological descriptors and found that the texture variables were those that most contributed to genetic diversity. Similarly, the T1 variable (Laws: ER) was one of the variables that most contributed to genetic diversity, in this study.…”
Section: Digital Phenotyping Meansmentioning
confidence: 99%
“…In general, the clusters reflected the phenotypic variability observed in these species (Torres et al, 2019). The similarity rates were not so high since they are allogamous species, with sexual reproduction preferred, so there was manifest variability with no consistent formation of groups in terms of geographical origin or species, but there was lax distribution of the materials in terms of the evaluated municipalities, with inter-and intraspecific variability that can be used to obtain new planting materials.…”
Section: Resultsmentioning
confidence: 91%
“…Seed traits can be used in the initial investigation of genetic diversity. Great genetic variability was recorded in the grain productivity property based on genetic parameters (Nascimento-Júnior et al, 2018;Torres et al, 2019).…”
Section: Introductionmentioning
confidence: 99%